Christ is risen a three-part choir with string orchestration and piano accompaniment easter cantata for the Junior Youth Choir of Bethany Baptist Church, Cubao - Galano, Kimberly Mae A.; Guadalupe, Jocelyn T. (Quezon City College of Music, University of the Philippines Diliman, 2018)
The project is an action research that focuses on teaching the newly formed Bethany Baptist Church Cubao, Junior Youth Choir (JY) on how to properly sing as a chorale. It includes practice plans, vocalises, and three-part (SAT) arrangements, accompanied and a capella, of church hymns for an Easter Cantata. It focuses on helping the adolescents during the transition stage and is of great help especially for those churches that do not have a youth choir and want to start one.
Thesis (B.M. Music) -- University of the Philippines Diliman
Keywords: Choral singing -- Instruction and study